Kajian Transformasi Fisik, Sosial, dan Lingkungan Pada Wilayah Peri Urban Kecamatan Driyorejo - Siti Nuurlaily Rukmana; Kokoh Imanullah (REKA RUANG, 2021)
Driyorejo District is one of the areas in Gresik Regency which borders the Surabaya City. The existence of economic activities in the form of industry and close to Surabaya City causes people to prefer to live in suburban areas, this has an impact on physical, social and environmental transformation in suburban areas. The purpose of this study was to determine the physical, social and environmental transformation of WPU Driyorejo District in 2013, 2016, 2019. This study used a qualitative descriptive method with overlay analysis techniques, interpolation, LST algorithms. The results showed an increase in physical transformation seen every year. In 2013 the area of ​​built-up land reached 1414.5 hectares, increased in 2016 to 160.4 hectares, increased in 2019 to 1743.8 hectares. The social transformation that occurs in the WPU of Driyorejo District is fluctuating, where in 2013 the number of people working in the agricultural sector was 4,741 residents, increased in 2016 to 4,803, decreased in 2019 to 4740 residents. The results of the LST algorithm analysis show that the environmental transformation undergoes a fluctuating transformation, in 2013 the land surface temperature reached 28.8 C°, increased to 30.1 C°, decreased in 2019 to 29.2 C°.